2011
DOI: 10.1021/bm200401p
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Polyethylene Oxide/Cellulose Nanocrystal Composite Nanofibrous Mats with Homogeneous and Heterogeneous Microstructures

Abstract: An electrospinning process was successfully used to fabricate polyethylene oxide/cellulose nanocrystal (PEO/CNC) composite nanofibrous mats. Transition of homogeneous to heterogeneous microstructures was achieved by tailoring the concentration of PEO/CNC mixture in the solution from 5 to 7 wt %. Morphology investigation of the obtained nanofibers demonstrated that rod-shaped CNCs were well-dispersed in the as-spun nanofibers and highly aligned along the nanofiber long-axis. PEO/CNC nanofibers became more unifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
187
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 260 publications
(200 citation statements)
references
References 48 publications
(76 reference statements)
6
187
1
1
Order By: Relevance
“…It was found that humidity treatments on the PVA/CNC nanocomposite fibrous mats induced significant enhancement of strength as a result of the increased contact area and enhanced adhesion between the fibers (Peresin et al, 2010a). The heterogeneous fibrous mats composed of rigid-flexible bimodal PEO/CNC nanocomposite fibers was demonstrated to be higher in mechanical properties than their homogeneous counterparts (Zhou et al, 2011a). The reinforced mechanism was illustrated by morphology observation of the tensile process, as shown in Figure 7.…”
Section: Cncs Reinforced Synthetic Polymermentioning
confidence: 95%
See 2 more Smart Citations
“…It was found that humidity treatments on the PVA/CNC nanocomposite fibrous mats induced significant enhancement of strength as a result of the increased contact area and enhanced adhesion between the fibers (Peresin et al, 2010a). The heterogeneous fibrous mats composed of rigid-flexible bimodal PEO/CNC nanocomposite fibers was demonstrated to be higher in mechanical properties than their homogeneous counterparts (Zhou et al, 2011a). The reinforced mechanism was illustrated by morphology observation of the tensile process, as shown in Figure 7.…”
Section: Cncs Reinforced Synthetic Polymermentioning
confidence: 95%
“…Recently, wood-based CNCs with a diameter of 10 ± 3 nm and a length of 112 ± 26 nm were processed into electrospun PEO fibers (Zhou et al, 2011a). Figure 4 shows that rod-shaped CNCs without obvious aggregation are well-dispersed in the as-spun nanofibers.…”
Section: Cncs Reinforced Synthetic Polymermentioning
confidence: 99%
See 1 more Smart Citation
“…Interconnected fibers also improve the mechanical proper- ties of the fibrous materials [30], which are influenced by the structure of the fibers and the interactions between them, as well [31]. Enhancement of the mechanical parameters (tensile strength, yield stress, and Young's modulus) can be achieved in the presence of finer fibers (a nano-network) among the main fibers [32]. A major problem regarding the mechanical testing of electrospun micro-and nanofibrous materials is the lack of reliable standards for the performance of these tests.…”
Section: Mechanical Testing Of the Fibrous Materialsmentioning
confidence: 99%
“…Chirayil et al (2014) mentioned that the addition of nanocomposites into thermoplastic starch could enhance the tensile strength of the product significantly compared with pure isolated thermoplastic starch, and the addition of sugar beet chip nanofibrils isolated via high-pressure homogenization to a phenol formaldehyde and polyvinyl alcohol matrix demonstrated excellent reinforcement properties (Chirayil et al 2014). Therefore, it is essential to isolate the nanocellulose from its micro-scale raw material with the purpose of maximizing the potential of the cellulose source to become the useful composite materials such as polyethylene oxide/cellulose nanocrystal (PEO/CNC) (Zhou et al 2011) and poly(vinyl alcohol)/cellulose nanocrystal (PVA/CNC) (Huan et al 2016).…”
Section: Introductionmentioning
confidence: 99%